АНОПЛОЦЕФАЛИДОЗЫ (ANOPLOCEPHALODOSES) ЛОШАДЕЙ В УЗБЕКИСТАНЕ - Алламуратов, Б.; Алламуратова, З.; Урымбетов, А.А. (SCIENCE and SOCIETY, 2017)
The article deals with the horses’ decease caused by helminthes of three kinds that are called Anaplocephalidos of horses. Donkeys and mules are susceptible to the family of Anoplocephalidae helminths. Three kinds of the family Anoplocephalidae are (Anoplocephala magna), (Anoplocephala perfoliata) and rarely - (Paranoplocephala magna). The mucous membrane of a lean gut bluetongue is inflamed, bulked up, with centre reddening and it is plentifully covered by slime of horses.